2009
DOI: 10.1534/genetics.109.104760
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Nonessential Domain II of Initiator Protein, DnaA, in Replication Control

Abstract: The initiation of replication in bacteria is regulated via the initiator protein DnaA. ATP-bound DnaA binds to multiple sequences at the origin of replication, oriC, unwinding the DNA and promoting the binding of DnaB helicase. From an Escherichia coli mutant highly perturbed for replication control, obgETTn5-EZ seqAD, we isolated multiple spontaneous suppressor mutants with enhanced growth and viability. These suppressors suppressed the replication control defects of mutants in seqA alone and genetically mapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…For DnaA to span the distance between high and low affinity recognition sites, the flexible domain 2 linker [44] may be required to extend DnaA protomers attached by domain 1 interactions (Figure 3). Interestingly, it was recently shown that deletions in domain 2 reduce initiation efficiency [45]. Regulators such as DiaA may also promote pre-RC assembly at this stage [41 • ] by stabilizing the interaction between the anchoring and extended DnaA (Figure 3).…”
Section: Filling the Gap: A Model For Regulation Of Pre-rc Assembly Imentioning
confidence: 99%
“…For DnaA to span the distance between high and low affinity recognition sites, the flexible domain 2 linker [44] may be required to extend DnaA protomers attached by domain 1 interactions (Figure 3). Interestingly, it was recently shown that deletions in domain 2 reduce initiation efficiency [45]. Regulators such as DiaA may also promote pre-RC assembly at this stage [41 • ] by stabilizing the interaction between the anchoring and extended DnaA (Figure 3).…”
Section: Filling the Gap: A Model For Regulation Of Pre-rc Assembly Imentioning
confidence: 99%
“…molgen.mpg.de/ messer/), domain 2 (residues 90-130 of E. coli DnaA) is not conserved in amino acid sequence or length. For E. coli DnaA, the removal of residues 96 -120 in domain 2 leads to reduced activity in DNA replication, but deletion of other consecutive sequences from this region has no apparent effect on activity (Nozaki and Ogawa 2008;Molt et al 2009). These observations suggest that domain 2 acts as a flexible link between domains 1 and 3.…”
Section: Dnaa Is the Replication Initiator In Bacteriamentioning
confidence: 99%
“…Deletions placed in domain II can repress initiation (61), but a GFP-tag can be inserted into this domain without loss of viability (6). While Domain II has not been assigned any specific role, the linker region may accommodate the need to position Domain I over the wide range of distances that separate DnaA recognition sites within oriC , or allow some flexibility in positioning DnaB on single-stranded DNA.…”
Section: The Initiator Protein Dnaamentioning
confidence: 99%